Faster - Tillman, George, 1969-; Shafer, Martin; Glotzer, Liz.; Gayton, Tony, 1959-; Teitel, Robert; Gayton, Joe.; Johnson, Dwayne, 1972-; Thornton, Billy Bob.; Jackson-Cohen, Oliver, 1986-; Gugino, Carla, 1971-; Grace, Maggie, 1983-; Bloodgood, Moon.; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
After ten years in prison, Driver (Dwayne Johnson) has focused on one thing -- hunting down the people responsible for brutally murdering his brother. Now a free man with a terrifying purpose, he sets out to find and kill all those on his list. But on his heels are two men who will do anything to stop him -- a veteran cop (Billy Bob Thornton) and a hitman (Oliver Jackson-Cohen) who finds his match in this worthy opponent. Now, the hunter is also the hunted.
Videodisc release of the 2010 motion picture.
Special features: Alternate ending; Deleted scenes with director's intro.
Director of photography, Michael Grady ; editor, Dirk Westervelt ; music, Clint Mansell.
Dwayne Johnson, Billy Bob Thornton, Oliver Jackson-Cohen, Carla Gugino, Maggie Grace, Moon Bloodgood, Adewale Akinnuoye-Agbaje, Tom Berenger, Mike Epps.
MPAA rating: R; for strong violence, some drug use, and language.
DVD; region 1; anamorphic widescreen (2.40:1) presentation; Dolby Digital 5.1.
Keywords: Police -- Drama; Assassins -- Drama; Ex-convicts -- Drama; Revenge -- Drama; Police; DVD-Video discs; Feature films; Fiction films; Action and adventure films; Video recordings for the hearing impaired; Drama